2012
DOI: 10.1038/bmt.2012.10
|View full text |Cite
|
Sign up to set email alerts
|

Long-term outcome after autologous or allogeneic stem cell transplantation in patients with recurrent follicular lymphoma

Abstract: Thirty-five consecutive patients with follicular lymphoma (FL) receiving SCT at our institution between January 2000 and December 2010 were included in this study. At the time of presentation, 30 (86%) had advanced stage disease and 25 (71%) received three or more chemotherapy regimens prior to transplantation. In all, 12 (34%) patients were in complete response pre-SCT following salvage therapy. At the time of analysis (median follow-up 6 years from diagnosis and 4 years from transplantation), 24 patients wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 15 publications
0
14
0
Order By: Relevance
“…The 5-year post-transplant OS was 53 vs. 91.7%, while the PFS was 43 vs. 73.3%, for the AlloSCT and ASCT groups, respectively. However, Villa et al (Canadian Bone Marrow Transplant Group) described an OS of 46 vs. 65% and a PFS of 46 vs. 55% for the AlloSCT and the ASCT groups, respectively, at 5-year post-transplant [96,99]. Therefore, the AlloSCT series demonstrated an inferior result compared with that of ASCT, which was due in part to high treatment-related mortality (35 vs. 10% at 5 years, respectively) and also to heavily pre-treatment conditions [100].…”
Section: Treatment Treatment and Outcome In Historical Seriesmentioning
confidence: 99%
“…The 5-year post-transplant OS was 53 vs. 91.7%, while the PFS was 43 vs. 73.3%, for the AlloSCT and ASCT groups, respectively. However, Villa et al (Canadian Bone Marrow Transplant Group) described an OS of 46 vs. 65% and a PFS of 46 vs. 55% for the AlloSCT and the ASCT groups, respectively, at 5-year post-transplant [96,99]. Therefore, the AlloSCT series demonstrated an inferior result compared with that of ASCT, which was due in part to high treatment-related mortality (35 vs. 10% at 5 years, respectively) and also to heavily pre-treatment conditions [100].…”
Section: Treatment Treatment and Outcome In Historical Seriesmentioning
confidence: 99%
“…There is limited data toward identifying prognostic variables informing the decision between to two transplantation modalities in consolidation. Other groups have compared outcomes of first transplantation for rel/ref FL with either allo-HCT or HDT-ASCT in contemporary retrospective studies (Reddy et al , 2012; Evens et al , 2013; Robinson et al , 2013) and one prospective clinical trial. (Tomblyn et al , 2011) A single-centre study demonstrated superiority of HDT-ASCT compared to allo-HCT with small numbers of patients and relatively short follow-up (4 years from transplantation).…”
Section: Resultsmentioning
confidence: 99%
“…(Tomblyn et al , 2011) A single-centre study demonstrated superiority of HDT-ASCT compared to allo-HCT with small numbers of patients and relatively short follow-up (4 years from transplantation). (Reddy et al , 2012) A National Comprehensive Cancer Network retrospective analysis determined age >60 years and 3 or more prior lines of therapy as adverse prognostic factors in the HDT-ASCT group and the allo-HCT cohort experiencing a greater risk of death in multivariate analysis of 184 patients. (Evens et al , 2013) Of the five HDT-ASCT patients with > 3 prior lines of therapy in our series, one patient died of NRM and another experienced POD at 2 months and 18 months post-HDT-ASCT, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…A total of 363 abstracts were excluded because studies were noncomparative or included nonindolent histology, or the publication was a study protocol, commentary, editorial, or review. After a full text review, an additional 5 studies were excluded because of samples with heterogenous histology without subgroup data [40], incomplete outcomes [41,42], missing pretransformation histology data [43], or being duplicate [28], as well as 7 studies [29,30,33,34,35,44,45] with low-grade lymphoid malignancies without histologic transformation. Four comparative studies [retrospective (n = 3) and prospective (n = 1)] [31,32,46,48] were retained for the pooled analysis.…”
Section: Resultsmentioning
confidence: 99%
“…Despite its reasonable treatment response, relatively high transplant-related mortality (TRM; up to 30-40%), mainly from graft-versus-host disease and infectious complications, has limited its wide application, especially in the elderly and patients with comorbidities [28,29,30,31,32,33,34,35,36]. Currently, insufficient comparative data are available to guide clinicians in selecting the best SCT modality in transformed lymphoid malignancies.…”
Section: Introductionmentioning
confidence: 99%